2006
DOI: 10.1182/blood-2006-06-025999
|View full text |Cite
|
Sign up to set email alerts
|

Phase 2 trial of oral vorinostat (suberoylanilide hydroxamic acid, SAHA) for refractory cutaneous T-cell lymphoma (CTCL)

Abstract: The activity and safety of the histone deacetylase inhibitor vorinostat (suberoylanilide hydroxamic acid, SAHA) were evaluated in patients with refractory cutaneous T-cell lymphoma (CTCL). Group 1 received vorinostat 400 mg daily, group 2 received vorinostat 300 mg twice daily for 3 days with 4 days rest, and group 3 received vorinostat 300 mg twice daily for 14 days with 7 days rest followed by 200 mg twice daily. Treatment continued until disease progression or intolerable toxicity. The primary objective was… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

26
727
2
5

Year Published

2007
2007
2019
2019

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 1,024 publications
(760 citation statements)
references
References 26 publications
26
727
2
5
Order By: Relevance
“…Vorinostat is the first of the new HDACi to be approved by Food and Drug Administration for the clinical use in cancer patients, namely the treatment of cutaneous T-cell lymphoma (CTCL) (Duvic et al, 2007;Garber, 2007). In a phase II study with orally administered vorinostat on 33 previously treated patients with refractory cutaneous T-cell lymphoma, partial response were observed in eight patients (24.2%) and 14 of 31 evaluable patients (45.2%) had pruritis relief (Duvic et al, 2007).…”
Section: Clinical Development Of Hdacimentioning
confidence: 99%
See 1 more Smart Citation
“…Vorinostat is the first of the new HDACi to be approved by Food and Drug Administration for the clinical use in cancer patients, namely the treatment of cutaneous T-cell lymphoma (CTCL) (Duvic et al, 2007;Garber, 2007). In a phase II study with orally administered vorinostat on 33 previously treated patients with refractory cutaneous T-cell lymphoma, partial response were observed in eight patients (24.2%) and 14 of 31 evaluable patients (45.2%) had pruritis relief (Duvic et al, 2007).…”
Section: Clinical Development Of Hdacimentioning
confidence: 99%
“…In preclinical studies, resistance to HDACi-induced transformed cell death was observed in human bladder carcinoma cells (T24) and prostate cancer cells (PC3) (Butler et al, 2000;Richon et al, 2000;Xu et al, 2006). Although vorinostat achieved 24.2% response rate in a phase II trial on CTCL, a considerable proportion of patients with CTCL did not respond well (Duvic et al, 2007). Resistance has been observed in clinical trials with other HDACi in different tumors.…”
Section: The Resistance To Hdacimentioning
confidence: 99%
“…Early phase I studies of both vorinostat and romidepsin established their safety and potential efficacy in lymphoproliferative disorders, including CTCL [269], thus paving the way for larger phase II studies. An earlier phase II study established 400 mg of oral vorinostat once daily as the optimal dose that was investigated further in 74 previously treated patients with CTCL, most of whom (>80%) had advanced-stage disease [270,271]. The overall response rate was 30% for patients with advanced-stage disease and was associated with a median duration of response estimated to exceed 185 days.…”
Section: Hdac Inhibitorsmentioning
confidence: 99%
“…Several HDAC inhibitors are in clinical development where activity has been observed mainly in haematological malignancies. This has led to the recent approval of vorinostat (SAHA) for the treatment of cutaneous T-cell lymphoma (Duvic et al, 2007).…”
mentioning
confidence: 99%